Professional guidance for the effective labor insertion: of students from the commercial education major, term 2017 - España Chavarría, Carolina (2019)
This qualitative descriptive study took up the challenge of analyzing the professional guidance for the effective labor insertion: of students from the commercial education major, term 2017. To achieve this purpose it was necessaryto diagnose the connection between vocational guidance and employability in the university level of education, as well as, to determine the added value that provides vocational guidance and working context acknowledgment forprofessional projection of the target group. Without a doubt, inputs obtained in this study served as the basis for rethinking training activities in the field of vocational guidance as job placement support.